The definition of rape as an apple of discord in the Polish legal system - Jarocka, Marika (Studia Iuridica Toruniensia, 2021)
The definition of rape is highly controversial today. The one developed in the Polish legal system, differs in substance from that postulated in Art. 36 of the Convention on preventing and combating violence against women and domestic violence. With reference to the public perception of the crime under Article 197 of the Penal Code, it seems that the differences in both definitions need to be clarified. The article will be devoted to a thorough analysis of the provision of the crime under article 197 of the Criminal Code, Article 36 of the Convention, indicating their differences and considering the need to change the definition in the Polish Penal Code.